2006
DOI: 10.1212/01.wnl.0000230139.45304.eb
|View full text |Cite
|
Sign up to set email alerts
|

Verbal memory decline after temporal epilepsy surgery?

Abstract: The results provide evidence for a dynamic decline of verbal memory functions up to 2 years after left temporal lobectomy, which then levels off.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
69
1
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(81 citation statements)
references
References 37 publications
7
69
1
4
Order By: Relevance
“…Previous studies have consistently shown that verbal memory is likely to decrease following resection of the language-dominant left temporal lobe [24][25][26] . Alpherts et al 24 found that L-TLE patients showed an ongoing decline in the acquisition and consolidation of verbal memory for up to 2 years after surgery, while R-TLE patients initially showed a slight improvement in verbal memory, which vanished 2 years after surgery. However, the main limitation of that study was that they only examined the postoperative changes in general intelligence, memory, language and visual-motor functions and did not examine the changes in executive functioning after surgery.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have consistently shown that verbal memory is likely to decrease following resection of the language-dominant left temporal lobe [24][25][26] . Alpherts et al 24 found that L-TLE patients showed an ongoing decline in the acquisition and consolidation of verbal memory for up to 2 years after surgery, while R-TLE patients initially showed a slight improvement in verbal memory, which vanished 2 years after surgery. However, the main limitation of that study was that they only examined the postoperative changes in general intelligence, memory, language and visual-motor functions and did not examine the changes in executive functioning after surgery.…”
Section: Discussionmentioning
confidence: 95%
“…Longitudinal results in nonsurgical patients with focal symptomatic epilepsies indicate rather stable performance over time, although a decline depending on the seizure situation seems possible. 1,11,21,31,47 In surgical patients with epilepsy, it has been observed that after an initial postsurgical decline, cognitive functions are stable, 2,3 and in cases of seizure freedom, even tend to improve. 21 Another difference between the groups was the fact that surgery was not offered to the medical patients.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…Although many follow-up studies span up to 2 years after surgery, showing little or no group changes in IQ, [5][6][7][8] long-term follow-up studies commonly extrapolate outcome from only a few individuals because of considerable within-study variation in follow-up duration, [9][10][11] ranging from 6 months to 10 years. Previous studies have suggested that seizure frequency, 12 memory function, 13 and intelligence 11 may show late changes after temporal lobe surgery. Long-term follow-up studies are therefore required to determine the more stable levels of cognitive functioning, allowing for postsurgical recovery and functional reorganization.…”
mentioning
confidence: 96%